The prevalence of denture stomatitis in cigarette and hookah smokers and opium addicts: findings from Rafsanjan Cohort Study - Farimah Sardari; Parvin Khalili; Hamid Hakimi; Saadat Mahmoudaghaei; Pouya Abedi (BMC, 2021)
Abstract Background The aim of this study was to investigate the association of denture stomatitis prevalence with cigarette, hookah and opium consumption and also dose-response relationship between the cigarette smoking duration and odds of denture stomatitis in population of Rafsanjan cohort center. Methods This cross-sectional study based on data of Rafsanjan Cohort Study (RCS) with 10,000 participants. After applying inclusion and exclusion criteria, 1619 participants were included in the analysis. Data were collected by oral examination and completion of pre-designed questionnaires to assess denture hygiene, smoking behavior, opium use and some other exposure variables. Multivariable logistic regression models were fitted to investigate possible association of cigarette, hookah and opium consumption and denture stomatitis. Results Prevalence of denture stomatitis among all 1619 denture wearers was 21.6%. Cigarette smoking was associated with a higher odds of denture stomatitis, with the adjusted odds ratio (95% CI) of 2.29 (1.53-3.41). Also, dose-response increases were observed with the highest odds ratio in the 4th quartile for denture stomatitis (p-value < 0.001). Opium consumption was associated with a decreased odds of denture stomatitis (adjusted OR; 0.81, 95% CI 0.58-1.13) which was not statistically significant. Also interaction between opium consumption and cigarette smoking was not associated with higher odds of denture stomatitis (adjusted OR: 1.65, 95% CI 0.85-3.22). Conclusions Based on the findings of the present study, while cigarette smoking had a dose-response relationship with the increased odds of denture stomatitis; this association was not found with opium consumption.